ASSOCIATION BETWEEN DURATION AS A FISHERMAN, DISTANCE OF HEALTH FACILITIES AND SMOKING WITH PTERYGIUM'S DISEASE IN FISHERMAN IN BENGKULU - Dwi Putri Sulistiya Ningsih; Ida Rahmawati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Fishermen are a high risk group for developing pterygium. The high frequency of exposure to UV, wind, dust and sand when working makes the prevalence of pterygium among fishermen quite high. The city of Bengkulu, which is geographically located on the west coast of Sumatra Island which is directly facing the Indonesian Ocean, makes the majority of its population work as fishermen. Objectives: This study aims to determine the relationship between duration of being a fisherman, distance to health facilities and smoking with pterygium disease in a group of fishermen in, Bengkulu. Methods: Analytical observational research with case control design. The sample of 120 fishermen consisted of 40 cases and 80 controls, because researchers used a case-control ratio of 1:2. Sampling using purposive sampling method. The dependent variable was pterygium disease. Independent variables of duration as a fisherman, distance of health facilities and smoking. The research instrument uses a structured questionnaire that has been tested for validity and reliability with Alpha Cronbach value (0.996) > r table. Data were analyzed by Chi Square. Results: Based on the research results, it was found that there was a significant relationship with duration as a fisherman (? 21 years) (OR = 3.980; 95%CI = 1.404-11.284; p = 0.006) with pterygium disease. There is no relationship between smoking (OR = 1.246; 95%CI = 0.559-2.778; p = 0.590) with pterygium disease. There is a significant relationship between the distance of health facilities (OR = 5.133; 95%CI = 2.249-11.715; p = 0.000) with pterygium disease. Conclusion: The length of time working as a fisherman increases the risk of developing pterygium disease as the frequency of exposure to UV, dust, wind and sand increases. It is necessary to use personal protective equipment to reduce the risk of exposure and education from health workers so that the public can take good preventive measures.